Optimalisasi Pengendalian Tikus melalui Pemasangan RUBUHA di Desa Bentok Darat, Kalimantan Selatan - Muhammad Indar Pramudi; Yusriadi Marsuni; Saipul Abbas; Helda Orbani Rosa; Dewi Fitriyanti (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Rodent pests (Rattus spp.) are one of the main threats to agricultural productivity in Indonesia, including in Bentok Darat Village, South Kalimantan. The damage caused by these pests not only reduces crop yields but also increases farmers' dependence on chemical pesticides, which pose environmental risks. To address this issue, effective and environmentally friendly pest control methods are needed. One approach employed is the installation of Owl Houses (RUBUHA) as habitats for barn owls, natural predators of rodents. This community service program aims to optimize rodent pest control by installing RUBUHA on agricultural land. The activities involve students and the Alam Subur farmer group, including training on RUBUHA installation, facility maintenance, and monitoring its effectiveness in reducing rodent populations. Observations showed that the installation of RUBUHA significantly reduced rodent attacks on agricultural land. Additionally, this method successfully increased crop productivity by up to 30% and decreased the use of chemical pesticides. In conclusion, RUBUHA installation is an innovative and sustainable solution for rodent pest control, supporting environmentally friendly agricultural practices while enhancing farmers' welfare.